1979
DOI: 10.1111/j.1399-0039.1979.tb00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of B‐Cell‐Specific Alloantibodies in Pregnancy Sera in the Lymphocytotoxicity and the Indirect Immunofluorescence Techniques

Abstract: Two hundred and eight pregnancy sera were tested for the presence of antibodies specific for lymphocyte sub‐populations by using the isolated B and T lymphocytes from the women's mating partners. This was done by the microlymphocytotoxicity and the indirect immuno‐fluorescence techniques. Five sera (2.5%) reacted exclusively with B lymphocytes and sixty‐three sera (30.2%) reacted with both B and T lymphocytes; none of the sera was specific for T cells. Several sera, reacting with both B and T lymphocytes, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…A tendency to an increased incidence of cytotoxic antibodies was observed in the third pregnancy in both pre-and post-partum sera (non-significant difference, lowest p value = 0.056). This is in agreement with results reported by Terasaki et al (1970) but differ from those reported by others, such as Ahrons & Glarvind (1971) who found the highest levels of cytotoxic antibodies after the third pregnancy, and Decary et al (1979) who reported that the highest lcvels could be found in the second pregnancy. It has also been showed that the frequency of cytotoxic antibodies may be lower at the end of pregnancy (Vives et al 1976).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A tendency to an increased incidence of cytotoxic antibodies was observed in the third pregnancy in both pre-and post-partum sera (non-significant difference, lowest p value = 0.056). This is in agreement with results reported by Terasaki et al (1970) but differ from those reported by others, such as Ahrons & Glarvind (1971) who found the highest levels of cytotoxic antibodies after the third pregnancy, and Decary et al (1979) who reported that the highest lcvels could be found in the second pregnancy. It has also been showed that the frequency of cytotoxic antibodies may be lower at the end of pregnancy (Vives et al 1976).…”
Section: Discussionsupporting
confidence: 92%
“…The observed incidence of cytotoxic antibodies among Venezuelan Mestizo multiparous women (2S%) is within the limits previously reported in the literature which range from 7.3% (Nymand et al 1971) 21.6% (Decary et al 1979) up to 36% (Terasaki et al 1970). Thcrc is general agreement that foeto-maternal alloimmunization against HLA antigens occurs from the first pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…These are due to variations in immunization and the resultant outcomes. Values range from 7.3% to 36% (7.3%, Swedish women;[9] 18.7%, Caucasian women;[10] 21.6%, American women;[11] 29%, Mestizo women[11] and 9.6%, Warao women;[11] Venezulean women;[12] 36% USA women[13] and south Indian women 10.6%. [14] Another study detected anti-HLA antibodies in only 5% of women with successful pregnancies during the first trimester, compared with an antibody prevalence of 10% in women who miscarried.…”
Section: Discussionmentioning
confidence: 99%